Pengaruh Strategi Bisnis dan Financial Leverage terhadap Manajemen Laba dengan Corporate Governance sebagai Variabel Moderasi - Husnaini Dwi Wanri; Erinos NR (Universitas Negeri Padang, 2021)
This study aims to examine the effect of business strategy and financial leverage as moderated by corporate governance in predicting real earnings management. This type of research is a causal association with a quantitative approach. The population used in this study are all manufacturing companies listed in Bursa Efek Indonesia 2016-2019. The sampling technique in this study using the purposive sampling technique, there are 80 manufacturing companies used as research samples. The business strategy variables are measured by the cost leadership strategy model for the current year. Earnings management variables are calculated by aggregating the triggering factors for earnings management, namely sales manipulation, overproduction, and discretionary spending. The leverage variable is calculated by the ratio of debt to assets and the moderating variable is measured by the proportion of share ownership by the managerial party. The data used in this study is secondary data obtained from the company's financial statements obtained from the official website of the Indonesia Stock Exchange and the official website of each company. The analytical method used is the multiple regression method which is processed using the SPSS 16 application. The results show that business strategy, financial leverage has a significant positive effect on real earnings management, CG can increase or weaken the relationship between business strategy, leverage on real earnings management but not significantly